Ectopic fat in youth: The contribution of hepatic and pancreatic fat to metabolic disturbances. (9th January 2014) - Cohen, Michal; Syme, Catriona; Deforest, Meghan; Wells, Greg; Detzler, Garry; Cheng, Hai‐Ling; McCrindle, Brian; Hanley, Anthony; Hamilton, Jill
<x xml:space="preserve">Abstract</x> Objective To study the relationships between parameters of glucose and insulin metabolism and visceral and abdominal ectopic fat in youth. Methods A cross sectional study of 50 children (24 females), 8‐18 years old. Anthropometrics, body composition, blood‐work and visceral and ectopic fat by magnetic resonance imaging were assessed. Insulin secretion, insulin sensitivity and beta cell function were calculated from an oral glucose tolerance test. Results BMI z‐scores ranged between −1.3 and 4.5. The hepatic fat fraction (HFF) ranged between 0 and 36% and pancreatic fat fraction (PFF) between 0 and 14%. Visceral fat, HFF and PFF were associated with clinical and biochemical metabolic abnormalities, and correlated with markers of insulin sensitivity (r = −0.60, P < 0.01; r = −0.64, P < 0.01; r = −0.48, P < 0.01, respectively) insulin secretion (r = 0.55, P < 0.01; r = 0.57, P < 0.01; r = 0.41, P < 0.01, respectively), and beta cell function (r = −0.49, P < 0.01; r = −0.59, P < 0.01; r = −0.39, P < 0.01, respectively). Conclusions Accumulations of pancreatic and hepatic fat have complementary clinical consequences in youth. While visceral and hepatic fat demonstrated a dominant effect, even relatively small degrees of pancreatic fat deposition may contribute to metabolic alterations.